Metode Ahlu Ra’yi dan Ahlu Hadis dalam Menetapkan Hukum - Eril; Fadli; Andi Muh. Taqiyuddin BN; Fadly (Ethics and Law Journal: Business and Notary, 2023)
This research aims to reveal the history of the ahlu ra’yi and ahlu hadith priests and reveal the legal istinbath methods of ahlu ra’yi and ahlu hadith. This research is qualitative, and the type of research is library research. The data collection method used is a literature study. The research results show that; 1) Imam ahlu Ra’yi is Imam Abu Hanifah and Imam Ahlu Hadith is Imam Malik bin Anas with a different style of life, including his educational history, which influenced the Istinbath method between ahlu ra’yi and ahlu hadith. 2) The method of istinbath ahlu ra’yi is to take ascent by using and making the basis of the Qur'an, al-Sunnah, Opinions of the Companions, Qiyas, Istihsan, Ijma', and al-'Urf. As for the method of Istinbath Ahlu Hadith, that is taking as a basis by using and making the basis of the Qur'an, al-Sunnah, Ijma ahlu al-Madinah, Fatwa of the Companions, Khabar ahad, Qiyas, Istihsan, Maslahah mursalah, Sadd zara'i, Istishab , and Syar'u man Qablana. Keywords: Ahlu Ra’yi, Ahlu Hadis, Istinbat.   Abstrak Tujuan penelitian ini untuk mengungkap sejarah imam ahlu ra’yi dan ahlu hadis  dan mengungkap metode istinbath hukum ahlu ra’yi dan ahlu hadis. Penelitian ini merupakan penelitian kualitatif, jenis penelitian adalah library research. Metode pengumpulan data  yang digunakan adalah studi literatur. Hasil penelitian menunjukan bahwa; 1) Imam ahlu Ra’yi adalah imam Abu Hanifah dan Imam Ahlu Hadis adalah imam Malik bin Anas dengan corak kehidupan berbeda, diantaranya dalam riwayat pendidikan yang mempengaruhi metode Istinbath antara ahlu ra’yi dan ahlu hadis. 2) Metode istinbath ahlu ra’yi, yaitu beristinbat dengan menggunakan dan menjadikan sebagai dasar al- Qur’an, al-Sunnah, Pendapat para sahabat, Qiyas, Istihsan, Ijma’,dan  al-‘Urf.  Adapun metode Istinbath Ahlu Hadis, yaitu beristinbat dengan menggunakan dan menjadikan sebagai dasar al-Qur’an, al-Sunnah, Ijma ahlu al-Madinah, Fatwa para sahabat, Khabar ahad, Qiyas, Istihsan, Maslahah mursalah, Sadd zara’i, Istishab, dan Syar’u man Qablana. Kata Kunci: Ahlu Ra’yi, Ahlu Hadis, Istinbat.